Venous thromboembolism in the menopausal period - Stachowiak, Grzegorz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Venous thromboembolism (VTE) is treated shabbily in gynaecology of the menopausal period. Being a serious complication of neoplasms, operative procedures and – at last – menopausal hormone therapy (MHT), it is undoubtedly noteworthy and calls for in-depth knowledge.